Advancements in cancer immunotherapies targeting CD20: from pioneering monoclonal antibodies to chimeric antigen receptor-modified T cells - Dabkowska, Agnieszka; Domka, Krzysztof; Firczuk, Malgorzata (Frontiers in Immunology, 2024)
CD20 located predominantly on the B cells plays a crucial role in their development, differentiation, and activation, and serves as a key therapeutic target for the treatment of B-cell malignancies. The breakthrough of monoclonal antibodies directed against CD20, notably exemplified by rituximab, revolutionized the prognosis of B-cell malignancies. Rituximab, approved across various hematological malignancies, marked a paradigm shift in cancer treatment. In the current landscape, immunotherapies targeting CD20 continue to evolve rapidly. Beyond traditional mAbs, advancements include antibody-drug conjugates (ADCs), bispecific antibodies (BsAbs), and chimeric antigen receptor-modified (CAR) T cells. ADCs combine the precision of antibodies with the cytotoxic potential of drugs, presenting a promising avenue for enhanced therapeutic efficacy. BsAbs, particularly CD20xCD3 constructs, redirect cytotoxic T cells to eliminate cancer cells, thereby enhancing both precision and potency in their therapeutic action. CAR-T cells stand as a promising strategy for combatting hematological malignancies, representing one of the truly personalized therapeutic interventions. Many new therapies are currently being evaluated in clinical trials. This review serves as a comprehensive summary of CD20-targeted therapies, highlighting the progress and challenges that persist. Despite significant advancements, adverse events associated with these therapies and the development of resistance remain critical issues. Understanding and mitigating these challenges is paramount for the continued success of CD20-targeted immunotherapies.